2010
DOI: 10.1074/jbc.m110.139691
|View full text |Cite
|
Sign up to set email alerts
|

Aggregated Electronegative Low Density Lipoprotein in Human Plasma Shows a High Tendency toward Phospholipolysis and Particle Fusion

Abstract: Aggregation and fusion of lipoproteins trigger subendothelial retention of cholesterol, promoting atherosclerosis. The tendency of a lipoprotein to form fused particles is considered to be related to its atherogenic potential. We aimed to isolate and characterize aggregated and nonaggregated subfractions of LDL from human plasma, paying special attention to particle fusion mechanisms. Aggregated LDL was almost exclusively found in electronegative LDL (LDL(؊)), a minor modified LDL subfraction, but not in nativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 46 publications
3
47
1
3
Order By: Relevance
“…LDL(Ϫ) or oxidized LDL (oxLDL) were subjected to gel-filtration chromatography to separate aggregated (agLDL) and nonaggregated (nagLDL) fractions. Gel-filtration chromatography was performed using two on-line connected Superose 6 columns in an AKTA-FPLC system (GE Healthcare), as described previously (21). One ml of LDL(ϩ), LDL(Ϫ), or oxLDL at 1 g protein/liter was loaded into the columns and was eluted with buffer 10 mM Tris, 150 mM NaCl, 1 mM EDTA, 2 M BHT, pH 7.4, at a flow of 1 ml/min.…”
Section: Isolation Of Ldl Subfractionsmentioning
confidence: 99%
“…LDL(Ϫ) or oxidized LDL (oxLDL) were subjected to gel-filtration chromatography to separate aggregated (agLDL) and nonaggregated (nagLDL) fractions. Gel-filtration chromatography was performed using two on-line connected Superose 6 columns in an AKTA-FPLC system (GE Healthcare), as described previously (21). One ml of LDL(ϩ), LDL(Ϫ), or oxLDL at 1 g protein/liter was loaded into the columns and was eluted with buffer 10 mM Tris, 150 mM NaCl, 1 mM EDTA, 2 M BHT, pH 7.4, at a flow of 1 ml/min.…”
Section: Isolation Of Ldl Subfractionsmentioning
confidence: 99%
“…On the other hand, PAF-AH, which has a 5-10-fold higher activity in LDL(-) than in native LDL, could also play a role in increasing the content of LPC and NEFA and in the generation of LDL(-) Sanchez-Quesada, 2005). Some type of SMase activity could also be involved in LDL(-) generation since a minor subfraction of LDL(-) is aggregated (Bancells, 2010b). It has been reported that LDL(-) has an intrinsic phospholipase C-like (PLC-like) activity that degrades with high affinity both SM and LPC (Bancells, 2008).…”
Section: Lipolysismentioning
confidence: 99%
“…Some characteristics in LDL(-) are involved in this higher affinity. Aggregation of lipoproteins favors PG binding, and LDL(-) has a high tendency to aggregate (Bancells, 2010b). In fact, a subfraction of aggregated LDL(-) is responsible for the binding to PG (Bancells, 2009).…”
Section: Binding To Proteoglycansmentioning
confidence: 99%
See 2 more Smart Citations